National Geographic field guide to the birds of North America - Dunn, Jon L. (Jon Lloyd), 1954-; Alderfer, Jonathan K. (National Geographic Society, 2011)
Presents a guidebook which provides identification tips, information on behavior and nesting, locator and range maps, and plumage and species classification data on over 990 species of birds found in North America.